Determinant of Unintended Pregnancy in Indonesia - Lubis, Pika Novriani; Djuwita, Ratna; Adisasmita, Asri C.; Ronoatmodjo, Sudarto; Gayatri, Maria (UI Scholars Hub, 2024)
Background: Unintended pregnancy is a global health problem. The number of unintended pregnancies globally is still high, accounting for 1 in 4 pregnancies. In Indonesia, it occupies 15% of total pregnancies. However, studies discussing the determinants of unintended pregnancies in Indonesia were conducted on a small scale. Methods: This cross-sectional research utilized the data of 15,316 respondents of the 2017 Indonesia Demographic and Health Survey. Results: The prevalence of unintended pregnancies in women with live births in the last 3–5 years was approximately 16%. The highest risk of unintended pregnancies was recorded for those with the youngest age, living in urban, and were grand multipara and for the couples who did not know each other’s preferences. Conclusions: Strengthening communication, information, and education in family planning programs, particularly for young women and grand multipara and promoting men’s involvement can help prevent unintended pregnancies.